A novel phenolic derivative inhibits AHL-dependent quorum sensing signaling in Pseudomonas aeruginosa - Bernabè, Giulia; Marzaro, Giovanni; Di Pietra, Giuseppe; Otero, Ana; Bellato, Massimo; Pauletto, Anthony; Scarpa, Melania; Sut, Stefania; Chilin, Adriana; Dall’Acqua, Stefano; Brun, Paola; Castagliuolo, Ignazio (Frontiers in Pharmacology, 2022)
Increasing antibiotic resistance and the decline in the pharmaceutical industry's investments have amplified the need for novel treatments for multidrug-resistant bacteria. Quorum sensing (QS) inhibitors reduce pathogens’ virulence without selective pressure on bacteria and provide an alternative to conventional antibiotic-based therapies. P. aeruginosa uses complex QS signaling to control virulence and biofilm formation. We aimed to identify inhibitors of P. aeruginosa QS acting on acyl-homoserine lactones (AHL)-mediated circuits. Bioluminescence and qRT-PCR assays were employed to screen a library of 81 small phenolic derivatives to reduce AHL-dependent signaling. We identified GM-50 as the most active compound inhibiting the expression of AHL-regulated genes but devoid of cytotoxic activity in human epithelial cells and biocidal effects on bacteria. GM-50 reduces virulence factors such as rhamnolipids, pyocyanin, elastase secretion, and swarming motility in P. aeruginosa PAO1 laboratory strain. By molecular docking, we provide evidence that GM-50 highly interacts with RhlR. GM-50 significantly improved aztreonam-mediated biofilm disruption. Moreover, GM-50 prevents adhesion of PAO1 and inflammatory damage in the human A549 cell line and protects Galleria mellonella from PAO1-mediated killing. GM-50 significantly reduces virulence factors in 20 P. aeruginosa clinical isolates from patients with respiratory tract infections. In conclusion, GM-50 inhibits AHL-signaling, reduces virulence factors, enhances the anti-biofilm activity of aztreonam, and protects G. mellonella larvae from damage induced by P. aeruginosa. Since GM-50 is active on clinical strains, it represents a starting point for identifying and developing new phenolic derivatives acting as QS-inhibitors in P. aeruginosa infections.